Website design: place for luxury brands in cyberspace?. Issue 12 (1st December 2016) - Shen, Kathy Ning; Vel, Prakash; Khalifa, Mohamed
ABSTRACT: A great challenge for luxury marketers is how to harness Internet's incredible influence on customers while still maintaining and adhering to the customer-based brand equity (CBE) of luxury brands. This study aims to investigate the effect of website design on the CBE of luxury brands. Integrating the research on aesthetic design and luxury branding, we develop and empirically validate a research model, specifying that two aesthetic design dimensions (aesthetic formality and aesthetic appeal) can stimulate a strong sense of luxury, which in turn leads to a positive evaluation of CBE. Furthermore, the effect of aesthetic design on the sense of luxury is contingent upon brand familiarity prior to the exposure of a luxury brand website. The research model is validated with a survey study involving 201 participants. The paper includes implications for website design to deliver online brand experience and develop CBE with specific online consumer groups. As an early attempt to examine the website design effect on online branding experience and brand equity, this study contributes to both literature of website aesthetics and online luxury branding.